2012
DOI: 10.1002/anie.201108199
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐Finger Proteins for Site‐Specific Protein Positioning on DNA‐Origami Structures

Abstract: Point the finger: Zinc‐finger proteins are convenient and site‐selective adaptors for targeting specific locations within DNA‐origami structures. Orthogonal targeting of the specific locations in the structures was demonstrated by using two adaptors, and the application of Escherichia coli lysate that contained the adaptor‐fused proteins successfully afforded the expected protein–DNA assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 50 publications
0
90
0
1
Order By: Relevance
“…36 The use of strong domain interactions (Zinc-finger for example) is another approach for site-specific protein-oligo coupling and can be achieved by tethering one binding domain to a protein, and the other binding domain to an oligonucleotide. 3738 The versatility of DNA nanostructures has also been used to improve the binding affinity between molecules. The assembly of a multi-valent ligand complex was achieved by combining several individual ligands on a DNA nanostructure, where the distance between ligands was carefully controlled.…”
Section: Dna-directed Self-assemblymentioning
confidence: 99%
“…36 The use of strong domain interactions (Zinc-finger for example) is another approach for site-specific protein-oligo coupling and can be achieved by tethering one binding domain to a protein, and the other binding domain to an oligonucleotide. 3738 The versatility of DNA nanostructures has also been used to improve the binding affinity between molecules. The assembly of a multi-valent ligand complex was achieved by combining several individual ligands on a DNA nanostructure, where the distance between ligands was carefully controlled.…”
Section: Dna-directed Self-assemblymentioning
confidence: 99%
“…[51] Additionally, other labs have used DNA templates and zinc finger protein fusion to engineer metabolic pathways. [52] A major setback to the use of oligomer scaffolds to alter cellular pathways is the requirement that the protein of interest be genetically tagged, thus not allowing for the reorganization of endogenous signaling pathways. In summary, the precision of base pairing, the diversity of oligonucleotide nanostructures and the ease of design has made DNA and RNA templates a helpful tool in scaffolding reactions from the molecular scale up to the organization of complex metabolic pathways, regardless of the obstacles associated with biocompatibility.…”
Section: Dna/rna Templated Reactionsmentioning
confidence: 99%
“…[10] A previous study showed site-specific positioning of ZnFs on DNA origami. [11] We used a ZnF, called QNK-QNK-RHR, showing a nanomolar affinity for dsDNA.…”
mentioning
confidence: 99%